Pemahaman dan Implementasi Standar Pengelolaan Pendidikan di Madrasah Ibtidaiyah - Arsyad; Sulfemi, Wahyu Bagja; Munthoi, Ahmad (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
The purpose of the study was to determine the level of understanding and implementation of Education Management Standards by Primary and Secondary Education Units, especially in Madrasah Ibtidaiyah. The research method uses descriptive qualitative, with data sources from the head of the madrasa, teachers, and the Madrasah Ibtidaiyah committee, Bogor Regency. The sampling technique used proportional cluster random sampling, with data collection methods using questionnaires and documentation studies. Data analysis used descriptive statistics. The results showed. First, the level of respondents' understanding of the regulation of Education Management Standards by the Primary and Secondary Education Units, namely the madrasah principal and Madrasah Ibtidaiyah teachers have sufficient understanding, while the Madrasah Ibtidaiyah committee has an understanding in the category of lack of understanding. The two respondents' assessments of the implementation of the Education Management Standards by the Primary and Secondary Education Units in Madrasah Ibtidaiyah, namely the head of Madrasah, teachers, and the Madrasah Ibtidaiyah committee generally considered that Madrasah Ibtidaiyah had not implemented governance according to the Education Management Standards by the Primary and Secondary Education Units. The implication of the results of this study is that the general understanding of respondents is only in the sufficient category, so the implementation of Madrasah Ibtidaiyah governance does not fully refer to the standards of education management by the Primary and Secondary Education Units. This shows that the level of achievement of educational management standards in Madrasah Ibtidaiyah is classified as not being achieved as a whole.